Development of a screening procedure for the characterization of Botryococcus braunii strains for biofuel application. Issue 11 (November 2016) - Moutel, Benjamin; Gonçalves, Olivier; Le Grand, Fabienne; Long, Marc; Soudant, Philippe; Legrand, Jack; Grizeau, Dominique; Pruvost, Jérémy
Graphical abstract: Highlights: A screening method adapted to Botryococcus characterization was proposed. Biomass, hydrocarbon and triacylglycerol productivities were measured in mini-PBR. Lipid class chemodiversity was measured by high-performance thin layer chromatography. B. braunii should be further investigated for its original polar lipid chemodiversity. Abstract: An integrated screening approach was developed to assess the potential of the Botryococcus genus for the production of lipids for biofuel application (hydrocarbons and triacylglycerols). The strategy developed in this study permitted to rigorously measure mandatory parameters for the determination of strain performance – i.e. growth rate and oil content. For that purpose, mini-photobioreactors run in parallel were used together with an exhaustive lipid class analysis. The quantitative productivity measurements indicated that the ten screened strains presented very different patterns in the conditions of PBR culture, firstly run in batch, and secondly in continuous mode. Indeed, with the applied setup, only four strains presented biomass productivities close to that previously measured for the reference strain 807/1 (between 74 and 307 mg L −1  day −1 of biomass for the tested strains). HC productivity obtained under continuous light (∼14 mg L −1  day −1 ) was close to that measured for the strain 807/1 (∼20 mg L −1  day −1 ), confirming B. braunii tested strains potential for biofuel application. The analysis of the lipid chemodiversity revealed moreover that this genus should be further investigated for its polar lipids, as it suggests potential pharmaceutical applications such as production of antitumorals or immunosuppressors.